2011
DOI: 10.1016/j.oceaneng.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Wave height forecasting in Dayyer, the Persian Gulf

Abstract: Forecasting of wave parameters is necessary for many marine and coastal operations.Different forecasting methodologies have been developed using the wind and wave characteristics. In this paper, Artificial Neural Network (ANN) as a robust data learning method is used to forecast the wave height for the next 3, 6, 12 and 24 hours in the Persian Gulf. To determine the effective parameters, different models with various combinations of input parameters were considered. Parameters such as wind speed, direction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…Our preliminary modelling showed that even though it is possible to have ANN models with three outputs, the accuracy generally decreases due to the complexity of the network. This finding is in line with the existing knowledge about the performance of ANN networks (Asma et al, 2012;Kamranzad et al, 2011;Zamani et al, 2008).…”
Section: Study Area and Evaluation Of The Datasupporting
confidence: 91%
“…Our preliminary modelling showed that even though it is possible to have ANN models with three outputs, the accuracy generally decreases due to the complexity of the network. This finding is in line with the existing knowledge about the performance of ANN networks (Asma et al, 2012;Kamranzad et al, 2011;Zamani et al, 2008).…”
Section: Study Area and Evaluation Of The Datasupporting
confidence: 91%
“…ANN has been the popular method for researchers to help them to solve prediction problem [21]. Architecture ANN has layer and neuron.…”
Section: Wide Genetic Algorithm Artificial Neural Networkmentioning
confidence: 99%
“…The ANN is a nonlinear mathematical model with the ability to simulate the biological neurons of the human brain (Kamranzad, Etemad-Shahidi, & Kazeminezhad, 2011). Each neuron input in hidden layers or output layer is multiplied by a corresponding interconnection weight, and then a bias (threshold) is added to the sum of the products:…”
Section: Artificial Neural Network (Anns)mentioning
confidence: 99%